Functions and Diseases of the Retinal Pigment Epithelium - Yang, Song; Zhou, Jun; Li, Dengwen (Frontiers in Pharmacology, 2021)
The retinal pigment epithelium is a fundamental component of the retina that plays essential roles in visual functions. Damage to the structure and function of the retinal pigment epithelium leads to a variety of retinopathies, and there is currently no curative therapy for these disorders. Therefore, studying the relationship between the development, function, and pathobiology of the retinal pigment epithelium is important for the prevention and treatment of retinopathies. Here we review the development and function of retinal pigment epithelium and its relevance to the pathobiology and possible treatment of retinopathies. In doing so, we provide new viewpoints outlining new ideas for the future study and treatment of retinopathy.